Rancang Bangun Sistem Informasi Manajemen Praktik Mandiri Dokter Gigi Berbasis Website - Fitriana, Devi; Rahmadi, Agyl Ardi; Armin, Aidil Primasetya (Jurnal Ilmu Siber dan Teknologi Digital, 2024)
Purpose: This study aims to develop a website-based dentist independent practice management information system that functions to improve the efficiency of the quality of data management and services at the Hary Alihkaryanto Dentist Independent Practice, which previously this practice still used paper-based manual methods which caused the data processing process to be slower and was at risk of data loss and damage. Methodology/approach: I This system was developed using the waterfall method which includes the stages of needs analysis, design, implementation, and testing. Functional testing of the system was carried out using the Blackbox Testing method while usability evaluation was carried out using the Umux Lite method. Results/findings: The results of system testing using the Blackbox Testing method all 10 test scenarios were successfully executed in accordance with the test cases and usability evaluation using the Umux Lite method resulted in a score of 84.28 which is included in the “A+” category, indicating a high level of user comfort and satisfaction. Conclutions: The developed system is able to improve efficiency and effectiveness in data management and support more optimal patient services. Limitations: The system is not yet equipped with a user role management feature, where patients do not have their own access in the system. Contribution: This research contributes to the field of health technology by presenting a service digitization model for dental practices, especially independent practices such as drg. Hary Alihkaryanto.